Multifunctional Wearable Thermoelectrics for Personal Thermal Management - Li, Lei; Liu, Wei‐Di; Liu, Qingfeng; Chen, Zhi‐Gang (Advanced functional materials, 2022)
With the ever‐increasing demand for wearable electronics and energy‐saving technologies, self‐powered thermoelectric personal thermal management (PTM) has attracted extensive research interest. In this review, the unique characteristics of thermoelectric PTM comparing with other technologies are first highlighted, and the key parameters and fundamental functions of thermoelectric PTM are systematically summarized. Then, the advances in thermoelectric PTM are overviewed from the material design to the wearable device design viewpoints. Finally, the key challenges and future research directions of thermoelectric PTM, where both high‐performance flexible materials and proper device designs are in urgent need, are pointed out. This review will deliver a systematic understanding and guideline for thermoelectric PTM. The increasing demand for wearable electronics has boosted the development of energy‐saving and self‐powered personal thermal management systems. This review highlights the unique advantages of thermoelectric technology comparing with other technologies, summarizes corresponding key parameters, fundamental functions, material and device advancements of thermoelectric personal thermal management, and further points out corresponding future research directions.